A new genus of Tainisopidae fam. nov. (Crustacea: Isopoda) from the Pilbara,Western Australia - Wilson, George D.f. (Zootaxa, 2003)
Isopod crustaceans from deep bores in calcrete aquifers of the Fortescue River drainages in the Pilbara Region (Western Australia) are found to be closely related to Tainisopus Wilson and Ponder, 1992, but represent a distinct taxon, Pygolabis humphreysi gen. nov., sp. nov. The two taxa provide information for a diagnosis of a new family of Flabellifera sensu lato, the Tainisopidae. Although similar to Tainisopus in many details, Pygolabis gen. nov. has tong-like uropodal endopods and an elongate pleotelson, thus lacking the presumably primitive condition of Tainisopus. The pleotelson of Pygolabis gen. nov. contains powerful muscles that cause the uropods to rotate medially, bringing the tong-like endopods together. Similar structures in other unrelated hypogean crustaceans are noted. Pygolabis gen. nov. has a highly complex appendix masculina on the endopod of male pleopod II, unlike the simple appendix masculina seen in Tainisopus.